Chitosan combined with calcium chloride impacts fresh-cut honeydew melon by stabilising nanostructures of sodium-carbonate-soluble pectin. (July 2015) - Chong, Jia Xin; Lai, Shaojuan; Yang, Hongshun
Abstract: Effects of chitosan, calcium chloride, and their combination on preventing quality and safety deterioration of postharvest fresh-cut honeydew melon at 7 °C were investigated. Treatments of all these three delayed weight loss, improved firmness, delayed colour changes and moderately inhibited microbial growth. Interestingly, combined treatment of chitosan and calcium chloride was the most effective, leading to 40% less weight loss, 45% (3.70 N) increase in firmness, less overall colour difference, and more than 0.5 log CFU/g inhibition on mesophilic and psychrotropic growths on day 13 of storage as compared to control group. In addition, these treatments also inhibited degradation of pectin chains. Nanostructural analysis of fruit pectin via atomic force microscopy (AFM) indicated that firmness was closely related to the nanostructure of sodium carbonate-soluble pectin (SSP). Short and narrow SSP chains were observed more in samples with less firmness. We conclude that edible coating of chitosan combined with calcium chloride treatment synergistically extends the shelf-life of fresh-cut honeydew melon by maintaining the integrity of SSP via interactions between SSP and calcium ions or protonated chitosan groups. Highlights: Chitosan combined with calcium as edible coating was applied for fresh-cut honeydew. Coating extended the physicochemical property changes of honeydew. Coating inhibited microbial growth on honeydew. Coating extended nanostructural degradation of pectin of honeydew.